Voltage Stability Analysis of Electric Power System with Integration of Renewable Energy - Mohamad Nor, Ahmad Fateh; Ramlee, Raudhah Izatee (Evolution in Electrical and Electronic Engineering, 2020)
This study presents an analysis of voltage stability of the electrical power system with the integration of renewable energy and the improvement of the conventional analysis using the artificial neural network (ANN), which is mainly focused on the effect of distributed generator-solar (DG-Solar) towards the electric power system. Real power and reactive power margins of both voltage stability are expressed as VSM (P) and VSM (Q), respectively. They are obtained from the actual power-voltage (PV) and reactive-power (QV) curve, which is created for each series by a series of load flows by incrementing P and Q load. Then, the system will integrate with 5MW, 50MW and 100MW of DG-Solar to compare the electric power system before and after the integration. The results are observed and compared for both situations. After that, an analysis improvement is made by using ANN-based model to predict the values of VSM (P) and VSM (Q) without having to perform PV QV Curve and calculate VSM (P) and VSM (Q). IEEE 30-bus was chosen as the electrical power system. The load flow analysis and ANN-based model are simulated and developed by using MATLAB software.